Monitoring and evaluation of the Local Technical Agroclimatic Committees (MTA) in Guatemala - 2022 - Hernández Quevedo, Mónica; Navarro Racines, Carlos Eduardo; Ajquejay, Sonia; Giraldo, Diana; Ramírez Villegas, Julián Armando (2022)
It is necessary to continuously monitor and evaluate the development of climate services in countries where CGIAR and its partners promote different approaches related to these. Here we show the application of a monitoring and evaluation instrument that has the objective of analyzing the scope, effectiveness, perception, and relevance of the Local Technical Agroclimatic Committees (MTA, initials in Spanish) of Guatemala. The instrument was effectively applied to nearly 300 participants from the Guatemalan MTAs to assess the fundamental aspects that must be taken into account for the proper functioning of the committees in the country, as well as the challenges and barriers faced by co-production, transfer, translation, and use of agroclimatic information. The results generally show a high adoption by users of the climate services promoted in Guatemala, highlighting their usefulness and relevance in the country.